Measurement of Human Work Reliability Using Systematic Human Error Reduction and Prediction Approach and Human Error Assessment and Reduction Technique Method - Bakhtiar, Bakhtiar; Syukriah, Syukriah; Iqbal, Muhammad (Malikussaleh University, Aceh, Indonesia, 2022)
CV. Raja Hati is a company that is engaged in the process of refinishing tires that have been bald into new ones. The tire retreading process has a relatively high percentage of defects, such as 14.8% Printing Process, 12.3% Surface Leveling, 8.6% Tire Curing, and so on. The problems in this study are the factors that cause defects in terms of human aspects, the types of errors that most often occur in the production process, and the value of human error probability (HEP) in the production process at CV. Raja Hati. This study aims to determine the factors that cause defects in terms of human aspects, the types of errors that most often occur in the production process and the value of human error probability (HEP) in the production process. The research was conducted using the SHERPA and HEART methods. The SHERPA method’s study results show that the types of errors that often occur in the tire retreading process are many wrong operator actions. Still, on the proper object (A7), the operator is wrong in dividing the time in doing work (A2), and the operator is not suitable for doing his job (A5). This study concludes that the factors that cause product defects in the tire retreading process are the absence of a procedure for correcting errors by 21.63%, the need for different techniques in doing work to facilitate operators by 27.04%, inexperienced operators by 12.36%, and inexperience and independent inspection has a percentage of 12.36%. The results of the calculation of the HEP value show that the average HEP value in the tire retreading process is 0.8552 or 85.52%, while the operator reliability value is 14.48%.